A Dual-Factor Analysis of Impulsive Purchasing Among Fteks Students on TikTok Shop: With Positive Emotions as A Moderator - Reza Febrina Agustin; Delyardi Nur; Rita Zunarti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines the effect of sales promotion and Electronic Word of Mouth (E-WOM) on impulsive buying behavior among FTEKS students at Universitas Muhammadiyah Muara Bungo, with positive emotion as a moderating variable. A quantitative approach was employed using a survey method. Data were collected from 247 respondents through purposive sampling and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings reveal that sales promotion and positive emotion significantly influence impulsive buying behavior, while E-WOM has no significant effect. Positive emotion also significantly moderates the relationship between sales promotion and impulsive buying with a weakening effect, but does not moderate the relationship between E-WOM and impulsive buying. These findings contribute to the development of Stimulus-Organism-Response (SOR) theory in the context of social commerce and provide practical implications for digital marketing strategies on TikTok Shop.